Reproduction by seed and clonality in plants: correlated syndromes or independent strategies?. (6th September 2016) - Herben, Tomáš; Tackenberg, Oliver; Klimešová, Jitka
Summary: We examine the relationships of traits of seed reproduction to traits of clonal growth and bud banks. Although there are a number of functional differences between these sets of traits underlying two different modes of reproduction, they both constitute a response to ecological gradients, which makes them potentially interdependent. We performed phylogenetic regressions of seed traits and traits of bud banks and clonal growth across the Central European flora. We took Ellenberg indicator values and indices of responses to disturbance as information on the positions of species optima along important ecological gradients. The analyses show that there are almost no relationships between these two groups of traits. This contrasts with the existence of strong correlations within these groups of traits which indicate specific syndromes of seed reproduction and of clonality. Both seed traits and traits of bud banks and clonal growth show fairly strong phylogenetic conservatism. The absence of correlations between individual groups of traits is at least partly due to the fact that each trait group shows relationships to different parameters of species' niches. Bud bank traits are determined by the disturbance niche of the species, clonal traits by soil and climatic factors, while seed traits show only weak correlations with the examined environmental factors if phylogeny is taken into account. Synthesis . The absence of integrated syndromes that would cover both seed reproduction and clonality across the flora implies that there are no selective forces that would affect both trait groups simultaneously. Clonal and bud bank traits are more tightly linked to species' niches, presumably because they are selected by local population processes only, in contrast to seed traits, which play a role also in dispersal. As the phylogenetic conservatism of clonal traits is almost as strong as the phylogenetic conservatism of seed traits, these traits do not serve as an evolutionarily more flexible alternative to seed reproduction. Abstract : By analysis of 900+ herbaceous species, we show existence of specific syndromes of seed reproduction and clonal growth, but no syndromes that cover both sets of traits. Clonal traits are more tightly linked to species' niches (namely disturbance niche) than seed traits. Phylogenetic conservatism of clonal traits is almost as strong as conservatism of seed traits, implying these traits cannot serve as an evolutionarily more flexible alternative to seed reproduction.